2022
DOI: 10.1155/2022/9883142
|View full text |Cite
|
Sign up to set email alerts
|

Differential Immunomodulatory Potential of Silver Nanoparticles and Effect on the Kynurenine Pathway in Male Wistar Rats

Abstract: Silver nanoparticles are increasingly being used in a wide variety of ways that may lead to frequency of exposure for humans and the environment. Thus, it is necessary to understand the biological effect(s) of these nanoparticles. Previously, we showed that AgNPs activated the kynurenine pathway in rat brain independently of oxidative stress in rats. This present study is aimed at evaluating the effect of AgNPs on some selected cytokines, redox parameters, and on the kynurenine level in rats. Male Wistar rats … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
2
1
Order By: Relevance
“…Contrary to other reports proving the role of AgNPs in oxidative stress, Adeyemi et al [ 39 ] reported that MDA and GSH levels were not significantly altered in AgNPs received rats compared with control rats. They thought that AgNPs might not cause oxidative stress nor alter the redox homeostasis in the rat brain.…”
Section: Discussioncontrasting
confidence: 64%
“…Contrary to other reports proving the role of AgNPs in oxidative stress, Adeyemi et al [ 39 ] reported that MDA and GSH levels were not significantly altered in AgNPs received rats compared with control rats. They thought that AgNPs might not cause oxidative stress nor alter the redox homeostasis in the rat brain.…”
Section: Discussioncontrasting
confidence: 64%
“…[ 52 ] Moreover, at high concentrations, NO is a powerful pro‐inflammatory mediator. [ 53 ] Increased levels of TNF‐α could stimulate NO production by upregulating inducible nitric oxide synthase (iNOS). [ 54 ] Nitric oxide (NO) functions at low intracellular concentrations as a signaling molecule in the endocrine system and pituitary secretion.…”
Section: Discussionmentioning
confidence: 99%
“…BBR has an essential role in controlling different autoimmune disorders due to its anti-inflammatory and immunomodulatory effects (Adeyemi, Afolabi et al 2022 ). Herbal medicines, particularly BBR, can potentially target inflammatory processes in DM, cancer, and neurological disorders with anti-inflammatory, immunomodulatory, and antioxidant effects.…”
Section: Introductionmentioning
confidence: 99%